2016
DOI: 10.1590/0074-02760150356
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of genotypes that determine resistance to macrolides, lincosamides, and streptogramins B compared with spiramycin susceptibility among erythromycin-resistant Staphylococcus epidermidis

Abstract: Coagulase-negative staphylococci, particularly Staphylococcus epidermidis, can be regarded as potential reservoirs of resistance genes for pathogenic strains, e.g., Staphylococcus aureus. The aim of this study was to assess the prevalence of different resistance phenotypes to macrolide, lincosamide, and streptogramins B (MLSB) antibiotics among erythromycin-resistant S. epidermidis, together with the evaluation of genes promoting the following different types of MLSB resistance:ermA, ermB, ermC,msrA, mphC, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 36 publications
3
24
1
Order By: Relevance
“…The erm C gene was the most common among all erm genes in both S. aureus and CNS exhibiting cMLSb or iMLSb phenotype. Similar data were reported by Juda et al ( 23 ). In Brazil, Coutinho et al ( 24 ) reported low frequency of the erm B gene, data which did not differ from our study.…”
Section: Discussionsupporting
confidence: 92%
“…The erm C gene was the most common among all erm genes in both S. aureus and CNS exhibiting cMLSb or iMLSb phenotype. Similar data were reported by Juda et al ( 23 ). In Brazil, Coutinho et al ( 24 ) reported low frequency of the erm B gene, data which did not differ from our study.…”
Section: Discussionsupporting
confidence: 92%
“…The study demonstrated that erythromycin reduced the number of Actinobacteria (including Corynebacterium and Propionibacterium ) while it only had a limited antibacterial effect on Staphylococci , potentially confirming the increased resistance of the bacterium to macrolides . But, the tested dermocosmetic not only reduced the number of Actinobacteria—it also reduced the number of Staphylococcus spp.…”
Section: Discussionmentioning
confidence: 86%
“…Minimal shifts in MIC for levofloxacin and up to 8-fold decrease in ciprofloxacin MIC indicate that NorA has minimal influence on fluoroquinolone resistance (Table S3) (Kaatz and Seo, 1995; Aeschlimann et al, 1999). mphC , a 2′-phosphotransferase which directly inactivates the macrolides via phosphorylation determines selective macrolide resistance (erythromycin) in UCH 121, UCH 127 and HH1184, all clonally distinct isolates(Matsuoka et al, 2003; Juda et al, 2016). mphC is not commonly reported to confer macrolide resistance in human S. aureus isolates, instead it is more frequently reported in agricultural studies (Li et al, 2015).…”
Section: Resultsmentioning
confidence: 99%